Bilateral Serous Psammocarcinoma of Ovary: Rare Variant Low Grade Serous Carcinoma - Saubhagya Kumar Jena; Pritinanda Mishra; Vandana Mohapatra; Sweta Singh (Case Reports in Obstetrics and Gynecology)
Serous psammocarcinoma is a rare variant of serous carcinoma arising from either ovary or peritoneum, characterized by massive psammoma body formation, low grade cytologic features, and invasiveness. Its clinical behavior is similar to serous borderline tumors with relatively favorable prognosis. We report herein a case of a 60-year-old postmenopausal woman who presented with abdominal distension. Contrast enhanced computed tomography (CECT) revealed calcified pelvic masses with ascites. Elevated serum CA-125 (970 U/mL) suggested malignant ovarian neoplasm. Patient underwent exploratory laparotomy with primary debulking surgery. Histopathology showed bilateral serous psammocarcinoma of ovary with invasive implants on omentum. Adjuvant chemotherapy was advised in view of advanced stage disease, although its benefits are poorly defined due to rarity of the tumor. However, patient opted out of it and is now on follow-up.